Statin-induced Myonecrosis—A Rare Adverse Effect of a Common Drug: A Case Report - Hanna Demissie; Kemal Ali; Dagnaw Mersha; Salhadin Mohammed; Winny Costa Mapour; Biruktawit Michael; Desalegn Yayeh; Biniyam A. Ayele (Sudan Journal of Medical Sciences)
Background: Clinically significant statin-induced myonecrosis is a rare clinical disorder that affects the skeletal muscles of patients taking statin medication. Its clinical presentation ranges from mild muscle pain to muscle weakness associated with significant elevation (>10×) of serum creatinine kinase (CK). Early screening, identification, and treatment of statin-induced myopathy are vital as it may lead to drug discontinuation and poor medication adherence.